AUDIT SISTEM INFORMASI MENGGUNAKAN KERANGKA KERJA COBIT 4.1 PADA PT. CINDYANI TIWI LESTARI - Kikye Martiwi Sukiakhy; anta rini utami; Cut Vita Rajiatul Jummi (Universitas Syiah Kuala, 2021)
The development of information systems has had a significant impact on various companies. Information systems that have been implemented are used to support business activities. This is also done by PT. Cindyani Tiwi Lestari, a company that has been established since 2014, is a company engaged in procurement services, quality improvement and problem solving for various heavy equipment. In this study the authors wanted to know whether the information system governance set by PT. Cindyani Tiwi Lestari is in accordance with the company's vision, mission, goals and objectives. The audit that has been carried out uses the Cobit 4.1 framework, especially in the delivery and support (DS) domain, because this domain includes security, data integrity, operational facilities and smooth system management. The technique of collecting data was carried out by observation, interviews and questionnaires. From the results of this study, the antidote will be obtained at the level of maturity (maturity level) at PT. Cindyani Tiwi Lestari, especially in the DS domain, which on average is at 1,510, this means that the process of the procedures applied has been developed in such a way and provides recommendations to the company to carry out regular checks. periodically and continuously on data in information systems related to company business processes.